Strategi Konservasi Daerah Tangkapan Air Bendung Ciliman Banten - Aditya Yumansyah; M Yanuar J Purwanto; Yudi Setiawan (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
The catchment area (DTA) of the Ciliman Dam in Banten is a source of water for the Ciliman Dam, so it needs to be conserved so that the reliability of Dam can be guaranteed. Changes in land use due to population growth in catchments have led to a decrease in forest area and increased land criticality. The forest area in the catchment is only 2.84% of the catchment area. The objectives of this study are (1) To identify the ecological, social and economic conditions of the Ciliman Dam catchment area; (2) Knowing the status of sustainability in the Ciliman Dam catchment area; (3) Develop sustainable Ciliman Dam catchment area with conservation strategies. The methods used include descriptive analysis, image interpretation, multi dimensional scaling (MDS) analysis, and SWOT analysis. The results of the analysis sustainability of the Ciliman Banten Dam catchment area showed quite sustainable results with a value of 52.52%, with a stress value of 12.98% and an R2 of 95.45%. Based on the results of leverage analysis that shows the value of the attributes that are most sensitive to the sustainability of the catchment area there are 7 attributes of the lever, among others in the ecological dimension there are 3 attributes namely land use, percentage of critical land, and forest area. On the economic dimension there are 2 attributes, namely the number of cooperatives and the farmer exchange rate (NTP), while on the social dimension there are 2 attributes, namely the unemployment rate and the level of education services. The SWOT analysis results for the internal factor analysis summary (IFAS) is 0.74 and the external factor analysis summary (EFAS) is 0.29. Based on the results above, the strategies that need to be implemented are maintain the population growth rate to increase the rate of economic growth in the Ciliman Dam catchment, increasing public knowledge about the importance of sustainable catchments, and utilizing vegetation cover that is still high enough to increase value forest economy for the community.